Growth of GaN on 123¯5-like Facets of Patterned Sapphire Substrate. (1st January 2017) - Wu, Pei-Yu; Chen, Chien-Chih; Huang, Chia-Yen; Kuo, Hao-Chung; Lin, Kun-Lin; Wu, YewChung Sermon
Abstract : GaN has been grown on wet-etched patterned sapphire substrate (PSS) by metal-organic chemical vapor deposition. It has been found that GaN was initiated not only from bottom c-facet but also from E 123 ¯ 5 facets of hexagonal patterns /pyramids. In this study, a vacancy-PSS on c-plane sapphire was used to investigate the growth of GaN on the E-like facets (E1 and E2) of distorted pyramids. The results show that the orientation relationship between E1-GaN and sapphire is (11 ¯ 2 6 ¯ )GaN // (1 ¯ 102 ¯ )sapphire and [1121 ¯ ]GaN // [112 ¯ 0]sapphire . At the same time, that between E2-GaN and sapphire is (011 ¯ 4 ¯ )GaN // (33 ¯ 06 ¯ )sapphire and [022 ¯ 1]GaN // [112 ¯ 0]sapphire .